Strategi Komunikasi Pemasaran Terpadu LPD Desa Adat Kelan dalam Mempertahankan Loyalitas Nasabah - Irva Dewi, Apricilia Ayu; Pascarani, Ni Nyoman Dewi; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT The purpose of this research to determine the marketing communication strategy used by the LPD Desa Adat Kelan in maintaining customer loyalty. This reasearch uses a qualitative approach. The technique of determining informants in this study used a purposive technique. Data obtained through in-depth interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion. The results of this study indicate that the integrated marketing communication strategy carried out by the LPD Desa Adat Kelan in maintaining customer loyalty focuses on sales promotion and public relations. While the advertising elements, personal sales, direct marketing, and interactive marketing are more aimed at introducing everything about LPDs and products in it. The marketing communication strategy that has been carried out is not yet integrated, considering that not all the elements used have the same message consistency. Keywords: LPD Desa Adat Kelan, Customer Loyalty, Integrated Marketing Communication Strategy (IMC)